2017
DOI: 10.1177/1758573217693974
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-traumatic stiffness of the shoulder following upper limb trauma with manipulation under anaesthetic

Abstract: MUA results for PTS following upper limb fracture are comparable to MUA for PFS. We therefore recommend MUA in PTS cases where conservative methods have failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…In a study of 73 patients undergoing open reduction internal fixation (ORIF) for proximal humerus fractures, Clavert et al 18 found that PTS developed in 4.1% of patients. In a study by Lancaster et al 19 on 64 patients with PTS after upper limb trauma, manipulation under anesthesia (MUA) was a successful intervention for improving ROM and Oxford Shoulder Scores. The improvement in ROM after MUA was similar to that observed in patients who underwent MUA for idiopathic AC.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In a study of 73 patients undergoing open reduction internal fixation (ORIF) for proximal humerus fractures, Clavert et al 18 found that PTS developed in 4.1% of patients. In a study by Lancaster et al 19 on 64 patients with PTS after upper limb trauma, manipulation under anesthesia (MUA) was a successful intervention for improving ROM and Oxford Shoulder Scores. The improvement in ROM after MUA was similar to that observed in patients who underwent MUA for idiopathic AC.…”
Section: Risk Factorsmentioning
confidence: 99%
“…These are different from other causes of stiffness, which may co-exist. A predisposition to inflammation, pain, prolonged immobilization, and other factors may additionally result in a chronic capsular fibrotic reaction ( 3 ). Soft tissue contractures may occur in various tissues including capsular synovial lining, and musculotendinous units.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The use of mobilization under anesthesia (MUA) is controversial. A study investigating the outcome of MUA in patients with primary frozen shoulder compared to those with refractory post-traumatic stiffness, including 55% of PHFs treated non-operatively, was reported ( 3 ). Both groups benefited from MUA, and no significant differences between the groups were found.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations